Higher serum phosphorus and calcium levels provide prognostic value in patients with acute myocardial infarction - Cao, Wei; Li, Yilan; Wen, Yao; Fang, Shaohong; Zhao, Bing; Zhang, Xiaoyuan; Zhang, Yanxiu; Lang, Xueyan; Yu, Bo; Zhang, Yao (Frontiers in Cardiovascular Medicine, 2022)
Background: Although traditional cardiovascular risk factors are closely related to the poor prognosis of acute myocardial infarction (AMI) patients, there are few studies on the relationship of serum phosphorus and calcium with prognosis in AMI patients. The relationship of serum phosphorus and calcium with prognostic biomarkers in AMI remains unclear. Methods and Results: A total of 3,891 AMI patients were enrolled from a prospective cohort study. We investigated the association of serum phosphorus and calcium with prognostic biomarkers. The risk of in-hospital heart failure (HF), postdischarge HF, all-cause mortality and cardiac mortality was estimated across quartiles of serum phosphorus and calcium levels. Serum phosphorus and calcium levels were associated with biomarkers of prognosis. Overall, 969 patients developed in-hospital HF during hospitalization, 549 patients developed postdischarge HF during a median follow-up of 12.17 months, and 252 patients died, with 170 cardiac deaths since admission. In the fully adjusted model, compared with patients in quartile 2 (Q2), patients with serum phosphorus levels in Q4 were at greater risk of postdischarge HF [sub-distributional hazard ratios (SHR) 1.55; 95% confidence interval (CI), 1.21-1.99], in-hospital HF [odds ratio (OR) 1.84; 95% CI, 1.47-2.31] and all-cause mortality(HR 1.59; 95% CI, 1.08-2.32) (all p-trend＜0.05). Compared with patients in Q2, patients with corrected calcium levels in Q4 had a higher risk of in-hospital HF (OR 1.62; 95% CI, 1.29-2.04), all-cause mortality (HR 1.99; 95% CI, 1.37-2.88) and cardiac mortality (SHR 1.87; 95% CI, 1.19-2.96) (all p-trend＜0.05). Conclusions: Serum phosphorus and calcium levels were associated with AMI prognostic biomarkers in AMI. Higher serum phosphorus was independently related to the increased risk of in-hospital HF, postdischarge HF and all-cause mortality, and higher serum calcium was independently related to the increased risk of in-hospital HF, all-cause mortality and cardiac mortality after AMI.